The habits of social networking site (SNS) use among postgraduate students - Rahim, Nor Zairah Ab B (Penerbit UTM Press, 2015)
The rise of social networking sites (SNSs) is currently overwhelming. Individuals are now able to interact, connect, and share information, photos, and other media in various SNSs. Facebook is one of the largest and most populated SNS in the world that is accessible by anyone including university students. Hence, it is interesting to understand the habits of use of such application by students, how they interact on these sites, and the nature of their influence on the deployment of Facebook into formal learning and as course communication tool. Findings from this research revealed that majority of the respondents use Facebook approximately 30 minutes to 2 hours daily. They also use Facebook not only to share entertainment materials but also communicating with their classmates on course related topics. Similar to the findings from another study, the students communicated on Facebook using a one-to-many style however in a more passive manner as most of the instances, they are not the creator of the content but only as viewer. This study could be extended to study more in-depth habits of SNS use by postgraduate students.